IMPACT OF ATMOSPHERIC EMISSIONS FROM THE ABAGUR SINTER FACTORY ON THE HEALTH RISK OF NOVOKUZNETSK RESIDENTS - Kislitsyna, Vera Victorovna; Surzhikov, Dmitry Vyacheslavovich; Golikov, Roman Anatolyevich; Motuz, Irena Yuryevna; Osipov, Viktor Dmitrievich (Medicine in Kuzbass, 2026)
The aim of the study was to determine the impact of atmospheric emissions from the Abagur Sinter Factory on the health of Novokuznetsk residents on the basis of a risk assessment.Materials and methods. The study was conducted using data from the volume of maximum permissible emissions of the Abagur Sinter Factory. To assess the risks, 40 exposure points were selected in different districts of the city. Calculations of maximum and average concentrations of pollutants in the atmospheric air generated by the sinter factory’s stationary sources at various points were performed using the ECOcenter-Standard software package. Maximum permissible concentrations were determined in accordance with Sanitary Rules and Norms 1.2.3.3685-21. Non-carcinogenic and individual carcinogenic risks were calculated according to Guideline 2.1.10.3968-23.Results. The calculated maximum and average pollutant concentrations at the selected points did not exceed the corresponding maximum permissible values. Hazard quotients for acute and chronic inhalation exposure to pollutants at various points corresponded to minimal or permissible (acceptable) risk levels. Hazard indices on critical organs and systems for acute and chronic inhalation exposure to pollutants were also at minimal or permissible (acceptable) levels. The total individual carcinogenic risk (1.11×10-6 to 8.11×10-5) corresponded to the permissible (acceptable) level.Conclusion. Atmospheric emissions from the Abagur Sinter Factory do not have a significant impact on the health of Novokuznetsk residents.
Keywords: Novokuznetsk; sinter factory; atmospheric emissions; pollutants; health risks